Fixing the Broken Phosphorus Cycle: Wastewater Remediation by Microalgal Polyphosphates - Slocombe, Stephen P.; Zúñiga-Burgos, Tatiana; Chu, Lili; Wood, Nicola J.; Camargo-Valero, Miller Alonso; Baker, Alison (Frontiers in Plant Science, 2020)
Phosphorus (P), in the form of phosphate derived from either inorganic (Pi) or organic phosphate (Po) is an essential macronutrient for all forms of life. P undergoes a biogeochemical cycle within the environment but anthropogenic redistribution through inefficient agricultural practice and inadequate nutrient recovery at wastewater treatment works have resulted in a sustained transfer of P from rock deposits to land and aquatic environments. Our present and near future supply of P is primarily mined from rock P reserves in geographically limited regions. To help ensure that this resource is adequate for humanity’s food security, an energy-efficient means of recovering P from waste and recycling it for agriculture is required. This will also help to address excess discharge to water bodies and the resulting eutrophication. Microalgae possess the advantage of polymeric inorganic polyphosphate (PolyP) storage which can potentially operate simultaneously with remediation of waste nitrogen and phosphorus streams and flue gases (CO2, SOx and NOx). Having high productivity in photoautotrophic, mixotrophic or heterotrophic growth modes, they can be harnessed in wastewater remediation strategies for biofuel production either directly (biodiesel) or in conjunction with anaerobic digestion (biogas) or dark fermentation (biohydrogen). Regulation of algal P uptake, storage and mobilization is intertwined with the cellular status of other macronutrients (e.g. nitrogen and sulphur) in addition to the manufacture of other storage products (e.g. carbohydrate and lipids) or macromolecules (e.g. cell wall). A greater understanding of controlling factors in this complex interaction is required to facilitate and improve P control, recovery and reuse from waste streams. The best understood algal genetic model is Chlamydomonas reinhardtii in terms of utility and shared resources. It also displays mixotrophic growth and advantageously, species of this genus are often found growing in wastewater treatment plants. In this review we focus primarily on the molecular and genetic aspects of PolyP and place this knowledge in the context of wastewater remediation and highlight developments and challenges in this field.